Economic potentials of energy-efficient residential building envelope retrofitting in Turkey - (:unkn) unknown (IGI Global, 2016)
The amount of energy consumption in the residential buildings has a very significant share with nearly 30 percent in the total amount of energy consumption. Therefore, residential sector is identified in this chapter as being one of the areas with a large potential for energy savings. Inefficient dwelling construction and design methods are widely used in Turkey and only about five percent of residential buildings are insulated. Concerning the importance and immediate need in Turkey for energy-efficient residential building retrofitting, this chapter identifies economic benefits of such retrofitting by particularly focusing on heat transfers by conductivity, where the rate can be determined by surface size, thermal resistance of the building materials and their thickness. © 2016 by IGI Global. All rights reserved.